Health-related quality of life and cost-of-illness in young people seeking peer support at @ease: A Dutch burden of disease study - Anouk Boonstra; Ghislaine A. P. G. van Mastrigt; Silvia M. A. A. Evers; Sander Osstyn; Remco F. P. de Winter; Nynke Boonstra; Therese A. M. J. van Amelsvoort; Sophie M. J. Leijdesdorff (PLoS ONE, 2026)
Introduction The burden of mental health problems remains largely unexplored among vulnerable young people, especially those seeking peer support. Accessing peer support is often a first form of help-seeking, allowing early identification of signs of distress. The lost (mental) health and expenses of these young people upon presenting for peer support can be revealed through monitoring of health-related quality of life (HRQoL) and costs of mental healthcare and productivity loss, examined in this study among young people visiting the @ease peer-to-peer walk-in centres in the Netherlands. Methods From @ease’s inception in January 2018 to mid-2024, a total of 940 answered questionnaires gathered through consecutive sampling contained minimally one required item. This bottom-up prevalence-based study focused on youth aged 12–30 who sought peer counselling at @ease. Burden of disease was estimated by: (1) HRQoL (EQ-5D-5L), and (2) Cost-of-illness through school absenteeism and mental healthcare use. Multiple imputation was used before conducting regression analyses, followed by non-parametric bootstrapping. This study expands upon an earlier publication that analysed data up to May 2019. Results HRQoL was impaired ( M = 0.64, SD = 0.24) and significantly lower if living alone or having parents with mental health problems, and higher if having a higher level of social and occupational functioning. In the three months before presenting, 35.2% of young people had been absent from school (3 days on average, costing €358 per individual) and 33.4% had visited mental healthcare (2 visits on average, costing €234 per individual). Total cost-of-illness was €1,501,743 annually, and €2,318 per individual. Mental healthcare costs were higher for those born in the Netherlands and without occupation, and school absenteeism costs were higher outside the COVID-19 pandemic and if not born in the Netherlands. Conclusions Found impairments and costs underscore the importance of investing in early-stage low-threshold services where substantial burden is already detectable, and of strengthening their capacity and links to stepped-care pathways to ensure timely support. Initiatives that help improve functioning and aid with challenging contexts may be advantageous in lowering the burden. Prospective (cost-)effectiveness studies are needed.